2018
DOI: 10.1186/s12870-018-1562-4
|View full text |Cite
|
Sign up to set email alerts
|

Dosage imbalance of B- and C-class genes causes petaloid-stamen relating to F1 hybrid variation

Abstract: BackgroundGreat advances have been achieved in our understanding of flower development and evolution since the establishment of the ABC model. However, it remains a challenge to define the exact context of organ identity in the component interactions of the ABC model.ResultsThrough hybridization, we detected a homeotic mutant in Petrocosmea (Gesneriaceae) uniquely displayed by the ‘petaloid-stamen’ in the third whorl with petal identity. Comparative Real-time PCR analyses demonstrate that both two B-class gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 82 publications
(77 reference statements)
1
17
0
Order By: Relevance
“…CvPI is essential for the specification of petal and stamen identity in Calluna vulgaris , and its reduced gene expression has been shown to result in the transition of petals into sepals 35 . In a homeotic mutant of Petrocosmea (Gesneriaceae), the dosage imbalance of B- and C-class genes—due to the upregulation of the two B-class genes DEFICIENS2 ( DEF2 ) and GLOBOSA ( GLO ) and the downregulation of the C-class gene PLE —caused the formation of petaloid stamens 36 . In rose ( Rosa hybrida ), suppression of the expression of RhAG increased the number of petals through the conversion of stamen petaloidy 37 .…”
Section: Introductionmentioning
confidence: 99%
“…CvPI is essential for the specification of petal and stamen identity in Calluna vulgaris , and its reduced gene expression has been shown to result in the transition of petals into sepals 35 . In a homeotic mutant of Petrocosmea (Gesneriaceae), the dosage imbalance of B- and C-class genes—due to the upregulation of the two B-class genes DEFICIENS2 ( DEF2 ) and GLOBOSA ( GLO ) and the downregulation of the C-class gene PLE —caused the formation of petaloid stamens 36 . In rose ( Rosa hybrida ), suppression of the expression of RhAG increased the number of petals through the conversion of stamen petaloidy 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous next studies [17,18] found that the reduction of anthers and pollen at an early stage of flower development is more detrimental to the size of the corolla of pistillate flowers in gynodioecious species compare with their degeneration at later stages. Additional confirmation of the mutual influence of the forming petals and stamens in the flower was convincingly demonstrated by ABC, and later by ABCDE, a molecular biological model of flower development [20]. According to the ABCDE model, the development of the calyx, corolla, androecium and gynoecium in the flowers is determined by genes belonging to the five classes (A, B, C, D, and E).…”
mentioning
confidence: 83%
“…According to the ABCDE model, the development of the calyx, corolla, androecium and gynoecium in the flowers is determined by genes belonging to the five classes (A, B, C, D, and E). At the same time, it has been shown that the products of the A + B + E genes are necessary for the formation of petals, and B + C + E for stamens [20]. Thus, there are at least two groups of genes (B and E) that determine the development of petals and stamens.…”
mentioning
confidence: 99%
“…‘Asa Blue’ (itself a cross between Petrocosmea flaccida and P. nervosa ) and P. chrysotricha raised by the American breeder Tim Tuttle. A study of more than 1500 flowers obtained from plants of P. glabristoma × P. sericea found 125 atypical flowers (Liu et al ., ). The authors concluded that imbalance between B‐ and C‐class genes caused petaloid stamen formation.…”
Section: Platementioning
confidence: 97%